Internet Marketing Terminology: Understanding The Key Terms for Success - Ramzbek Hamdamov (Scientific Trends, 2024)
In the dynamic and continually evolving field of digital marketing, a comprehensive understanding of key terminology is vital for professionals and businesses seeking to thrive in the online space. This study explores foundational concepts such as Search Engine Optimization (SEO), Pay-Per-Click (PPC) advertising, and Conversion Rate Optimization (CRO), among others, providing in-depth explanations and practical applications. The analysis emphasizes the interconnected nature of these terms and their role in shaping effective digital strategies. Using a structured approach, the article integrates definitions, examples, and visual aids to deliver actionable insights for marketers, scholars, and practitioners. By mastering these terms, stakeholders can enhance their marketing efficacy and achieve sustainable competitive advantages in the digital economy.
Keywords: Digital marketing, SEO, PPC, CRO, Social Media Marketing, Content Marketing, Online Advertising, Internet Marketing Strategy, ROI, CRM